Correlation between fingerprint patterns in type-II diabetes mellitus - Shamshuddin R. Kakkeri; Habibullah Attar; Javidulla Khan (Al Ameen Medical College, 2018)
Objective: To describe the association of Dermatoglyphics with type II Diabetic Disease and to support as evidence in court of law regarding identification of persons. Methodology: In this study one hundred type II Diabetes mellitus patients (50male and 50 female) were selected and compared with equal number of controls. Hand fingerprints were taken by Indian ink method. The Parameters such as arches, whorls, loops were studied. Fingerprint tip patterns are not same in Diabetics and controls. Result: Out of 100 Diabetic Mellitus type II patient's when compared frequency of Whorls was significantly increased in both hands of males and females around 67 %,whereas Loop with 26% and Arches least with 5%. Conclusion: The dermatoglyphic study revealed that majority of the patients were belonging to Whorl pattern of finger prints followed by patients belonging to Loop pattern and the least patterns were Arch. The results of the present research work indicate that dermatoglyphic abnormalities may be used as a diagnostic tool for predicting the possibility of the development of diabetes at a later date Personal identification is becoming increasingly important not only in legal medicine but also as evidence in the court of law in criminal investigation and identification.